The Dilemma of Inclusive Education: Inclusion for Some or Inclusion fo r All - Leijen, Äli; Arcidiacono, Francesco; Baucal, Aleksandar (Frontiers in Psychology, 2021)
In this paper, we intend to consider different understandings of inclu sive education that frame current public and professional debates as w ell as policies and practices. We analyze two – somewhat opposing – di scourses regarding inclusive education, namely, the “inclusion for som e” – which represents the idea that children with special needs have a right to the highest quality education which can be delivered by spec ially trained staff, and the “inclusion for all” – which represents th e idea that all children regarding their diverse needs should have the opportunity to learn together. To put the two discourses in a dialogi cal relation, we have reconstructed the inferential configurations of the arguments of each narrative to identify how the two definitions co ntribute to position children with and without special needs and their teachers. The results show the possibilities to bridge the two narrat ives, with respect to the voices they promote or silence, the power re lations they constitute, and the values and practices they enact or pr event.